Role of FKBP5 and its genetic mutations in stress-induced psychiatric disorders: an opportunity for drug discovery - Malekpour, Mahdi; Shekouh, Dorsa; Safavinia, Mohammad Ebrahim; Shiralipour, Shadi; Jalouli, Maryam; Mortezanejad, Sahar; Azarpira, Negar; Ebrahimi, Niloofar Dehdari (Frontiers in Psychiatry, 2023)
Stress-induced mental health disorders are increasingly growing. It is while psychiatric diseases are rarely diagnosed and as a result, drug therapy doesn’t occur sufficiently. There are many neurotransmitters, hormones, and mechanisms that are important in regulating the stress response of the body. One of the most important components of the stress response system is the hypothalamus-pituitary-adrenal (HPA) axis. FKBP prolyl isomerase 5 (FKBP5) is the negative regulator of the HPA axis and its effects have been noticed recently. FKBP5 negatively regulates the cortisol level (the end product of the HPA axis) which indirectly regulates the sensitivity of the HPA axis to stressors. Previous studies showed the influence of FKBP5 gene mutations and epigenetic changes in different psychiatric diseases and drug responses and suggest the FKBP5 protein as a drug target and biomarker for psychological disorders. In this review, we attempted to discuss the effects of the FKBP5 gene and its mutations on different psychiatric diseases and discuss about the effects of on the FKBP5 gene.